Near-infrared Raman Microspectroscopy Detects High-risk Human Papillomaviruses - Vargis, Elizabeth (Neoplasia Press Inc., 2012)
BACKGROUND: Detecting human papillomaviruses (HPVs) infection in cervical cells is an exceedingly important part of the clinical management of cervical dysplasia. Current guidelines in women's health outline the need for both the Papanicolaou test as well as high-risk HPV testing. Testing for HPV is expensive, is time-consuming, and requires experienced technicians. METHODS: Two sets of near-infrared Raman microspectroscopy experiments were conducted using a Raman confocal microscope system. First, Raman spectra were acquired from four different cell culture lines, two positive for HPV (HeLa, SiHa), one negative for HPV, but malignant (C33A), and one normal, HPV-negative line (NHEK). The three malignant lines were all derived from cervical cells. Second, Raman spectra were acquired from deidentified patient samples that were previously tested for the presence of high-risk HPV. RESULTS: The spectra from the cell culture lines and the patient samples contained many statistically significant differences. Using sparse multinomial logistic regression to classify the data led to classification accuracies of 89% to 97% for the cell culture samples and 98.5% for the patient samples. CONCLUSIONS: Raman micro-spectroscopy can be used to detect HPV and differentiate among specific HPV strains. This technique may provide health providers with a new method for quickly testing cell samples for the presence of HPV.